Six Novel O Genotypes from Shiga Toxin-Producing Escherichia coli - Iguchi, Atsushi; Iyoda, Sunao; Seto, Kazuko; Nishii, Hironobu; Ohnishi, Makoto; Mekata, Hirohisa; Ogura, Yoshitoshi; Hayashi, Tetsuya (Frontiers in Microbiology, 2016)
Serotyping is one of the typing techniques used to classify strains within the same species. O-serogroup diversification shows a strong association with the genetic diversity of O-antigen biosynthesis genes. In a previous study, based on the O-antigen biosynthesis gene cluster (O-AGC) sequences of 184 known Escherichia coli O serogroups (from O1 to O187), we developed a comprehensive and practical molecular O serogrouping (O genotyping) platform using a PCR method, named E. coli O-genotyping PCR. Although the validation assay using the PCR system showed that most of the tested strains were successfully classified into one of the O genotypes, it was impossible to classify 6.1% (35/575) of the strains, suggesting the presence of novel O genotypes. In this study, we conducted sequence analysis of O-AGCs from O-genotype untypeable Shiga toxin-producing E. coli (STEC) strains and identified six novel O genotypes; OgN1, OgN8, OgN9, OgN10, OgN12 and OgN31, with unique wzx and/or wzy O-antigen processing gene sequences. Additionally, to identify these novel O-genotypes, we designed specific PCR primers. A screen of O genotypes using O-genotype untypeable strains showed 13 STEC strains were classified into five novel O genotypes. The O genotyping at the molecular level of the O-AGC would aid in the characterization of E. coli isolates and will assist future studies in STEC epidemiology and phylogeny.